Description of the unknown males of three Chinese Meligethes (Coleoptera: Nitidulidae, Meligethinae) - Simone Sabatelli; Paolo Audisio; Josef Jelínek; Meike Liu; Min Huang (Fragmenta entomologica, 2020)
In this paper we present the description of male genitalia and additional information on taxonomy of three recently described and poorly known Chinese endemic members of the genus Meligethes Stephens, 1830, Meligethes (Odonthogethes) brassicogethoides Audisio, Sabatelli & Jelínek, 2015, M. (O.) inexpectatus Liu, Huang, Cline, Sabatelli & Audisio, 2017, and M. (O.) tricuspidatus Liu, Huang, Cline & Audisio, 2018.